Hello!
First, notice that as we have similar sides, we will also have similar sides. So:
EF is similar to HI
EG is similar to GH
FG is similar to GI
Notice that we know the measurement of four sides, so we can write it as a proportion, look:
![(EF)/(HI)=(EG)/(GH)](https://img.qammunity.org/2023/formulas/mathematics/college/8zmvphd1wt9k83jbvoj7kued87j2ojffaq.png)
Replacing with the values:
![(3)/(4)=(x+1)/(x+3)](https://img.qammunity.org/2023/formulas/mathematics/college/kww1vvhr1xb5qzuxbedbl4t5q701qt2bl2.png)
Multiplying it across:
![\begin{gathered} 3\cdot(x+3)=4(x+1) \\ 3x+9=4x+4 \\ 9-4=4x-3x \\ 5=x \\ x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kp210z4tz98n0tscxbt0vpf7dfqhyzh8o6.png)
Now, let's replace it to know the measurement of sides with unknowns (EG and GH):
![\begin{gathered} EG=x+1 \\ EG=5+1 \\ EG=6 \\ \\ GH=x+3 \\ GH=5+3 \\ GH=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/39k701hi4o0qm2px186gyokax30w7zni5q.png)
Right answer: third alternative.